Learners' Accessibility and Adaptability to Technology - Lumauag, Ramil G. (Asia Pacific Higher Education Research Journal (APHERJ), 2017)
This paper aims to describe the dynamics of learners in the use of technology specifi cally the internet, social media, and mobile devices in class and how they adapt to new technology and access information given of a new learning environment. This study used the qualitative method and an interview guide validated by identified experts was used to gather data from the twenty participants using purposive sampling. Results revealed that learners used technology as portal of knowledge wherein they can store and share documents, access lecture materials, view class announcements and submit class activities. The availability of online information motivates the learner to learn new concepts, and thereby promoted self-directed and independent learning. Learner shares signifi cant information wherein they collaborate and interact online using chat, messages, video call, and email. Unnecessary information on social media like spam, advertisements, negative post tends to distract the learners which lead them to wrong information. Since this study focused on the learners, a similar study is also recommended that will focus on the dynamics of teachers in the use of educational technology to describe their experiences, and how they adapt to the paradigmatic shift in instruction. It is also recommended to include ethical use of technology and social media.